Relation of Bcl-2 expression to androgen receptor, p21WAF1/CIP1, and cyclin D1 status in prostate cancer. Issue 1 (1st February 2000) - Kolář, Z; Murray, P G; Scott, K; Harrison, A; Vojtěšek, B; Dušek, J
Abstract : Background —There is currently no effective treatment for recurrent hormone refractory carcinomas of the prostate gland. An understanding of the underlying mechanisms responsible for the progression of these lesions is likely to be important for the development of new therapeutic approaches. Recently, it has been suggested that the transition to a hormone independent state is accompanied by increased proliferation and bcl-2 gene expression, as well as by a decreased apoptotic state. Aim —To investigate the possible role of Bcl-2 and other cell cycle regulating proteins in the development of prostatic tumours. Methods —Immunohistochemistry was used to study the relation between the expression of Bcl-2 and the androgen receptor, as well as p21WAF1/CIP1 (p21), and cyclin D1 status, in a series of 89 prostate cancer samples taken before androgen withdrawal treatment. Results —Androgen receptor negative tumours expressed significantly higher amounts of Bcl-2 than those prostate carcinomas with low/medium androgen receptor values. However, in tumours expressing the highest amounts of androgen receptor, Bcl-2 expression was also high. A significant positive relation between Bcl-2 and p21 expression, as well as an inverse relation between Bcl-2 and cyclin D1 expression, was noted. Androgen receptor positive samples also expressed significantly higher amounts of cyclin D1. Conclusions —These results suggest that p21 and cyclin D1 expression in prostatic cancer might be modulated by Bcl-2 and by androgens and in turn this could be relevant to the progression of prostatic cancer.